The application of biogas sludge as organic fertilizer on the grwoth of spinach plant (Amaranthus tricolor) - Nurzainah Ginting; E. Novilda; . Mustamu (Syiah Kuala University, 2012)
As North Sumatera Province has focused on agriculture in its development, a lot of agriculture researchs need to be conducted. A research of biogas sludge ( from cattle dung) application on spinach plants was done on February until April 2012. The research’s objective were to determine chemical quality of biogas sludge as organic fertilizer, the growth response of spinach plants and the economic benefits of biogas sludge. The research was used Completely Randomized Design (CRD) with seven replications and five treatments. The results showed that chemical quality of biogas sludge were as follows : N, P, K, C and pH 1.25% , 0.065, 0.097%, 27.26%, 9.02. C/N ration was 21.80. These chemical quality indicated biogas sludge can be used as good organic fertilizer. Data on average plant height, leaf number, canopy biomass and root biomass indicated that 250 ml per day biogas sludge could be an alternative of 2.5 g NPK as early fertilizer. The highest yield of five treatments was application of 250 ml biogas sludge with 2.5 g NPK at the beginning of spinach planting to the parameters plant height, canopy biomass and root biomass. Biogas sludge application on spinach plants in this research gave economic benefits as much as Rp. 205.554; which was obtained every 30 HST and R/C ratio was 2,93 means that every Rp. 1,- costs in spinach planted wil get Rp. 2,93,- revenue